2008
DOI: 10.1002/prca.200780097
|View full text |Cite
|
Sign up to set email alerts
|

A mass spectrometric strategy for profiling glycoproteinoses, Pompe disease, and sialic acid storage diseases

Abstract: Glycoproteinoses, Pompe disease, and sialic acid storage diseases are characterized by a massive accumulation of unprocessed oligosaccharides and/or glycoconjugates in urine. The identification of these glycocompounds is essential for a proper diagnosis. In this study, we investigated the potential of MALDI-TOF-MS to identify glycocompounds present in urine from patients with different inborn errors of glycan metabolism. Urinary glycocompounds were permethylated, and analyzed using GC-MS and MALDI-TOF-MS. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Indeed, it has previously been reported in chemically derivated urine (e.g. permethylated urines) that some oligosaccharides can be detected by mass spectrometry [30,41]. In our study, we found in urines from healthy subjects, with a similar abundant pattern, a set of intensive peaks for which no chemical composition could be identified.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Indeed, it has previously been reported in chemically derivated urine (e.g. permethylated urines) that some oligosaccharides can be detected by mass spectrometry [30,41]. In our study, we found in urines from healthy subjects, with a similar abundant pattern, a set of intensive peaks for which no chemical composition could be identified.…”
Section: Discussionsupporting
confidence: 59%
“…Efforts to improve the oligosaccharidosis screening have been achieved using mass spectrometry. For instance, the group of Michalski developed a strategy combining three different approaches with MALDI-TOF-MS and GC-MS after permethylation and enzymatic digestions to identify the glycocompounds accumulated in urine [30]. More recently, a method using PMP derivatization combined with LC-MS/MS has been adapted to screen oligosaccharidoses by selected reaction monitoring MS, and it revealed specific patterns corresponding to each disorder [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient report. Many truncated complex glycans lacking galactose and sialic acid (Nsibu, et al, 2008) Various Urinary glycans TOF (DHB), glycans (per-Me), GC/MS Development of method for profiling glycoproteinoses (Faid, et al, 2008) Unspecified Urine Q-TOF (THAP, NH 4 citrate), Glycans…”
Section: Agp From Serummentioning
confidence: 99%